Cristãos do reino de Deus em busca da prosperidade: uma guerra travada contra o Diabo - Machado, José Cristiano Matos (2022)
The present work proposes an investigation into the relationship between the Theology of Prosperity and the emphasis given to the figure of the Devil within the Universal Church of the Kingdom of God (from the Brazilian acronym IURD), as both cases configure distinctive characteristics of this religious institution. Considering the rapid growth of the neo-Pentecostal current in the country and the influence that the segment currently exerts on Brazilian society, this study becomes significant when it turns its gaze to the people who practice this religion. The interest in investigating the presence of the Theology of Prosperity and the emphasis given to the Devil in the doctrine of the Universal Church become relevant when we observe the way these two characteristics put the church in a complex doctrinal position, since all discourse around the Devil has a mystical character, while the reasoning behind the Theology of Prosperity is pragmatic. This finding has demanded an in-depth investigation of the IURD's doctrine regarding these two elements. In pursuit of the objective, we specifically seek: (i) to understand, through primary sources (reference materials produced by the church, television and radio programs and the institution's websites), the context that involves those who are faithful of the IURD; (ii) to investigate, through review of literature, which elements form the uniqueness of the idea of Devil conceived within the IURD; and (iii) to identify the concept of Theology of Prosperity in the doctrine of the institution and analyze the relationship established by the literature between the figure of the Devil and the Theology of Prosperity in the Universal Church. To broaden the understanding of the object of investigation, we turn our gaze to the discourse of those faithful to the church, since there is still a gap in this regard when it comes to academic works. Therefore, we chose to analyze videos posted on the digital video platform YouTube in which the faithful give their testimonies, based on the discursive information given by themselves about the blessings achieved in their lives. For this, we used as a methodological framework the Discourse Analysis, from which we built an instrument for the analysis of the collected data. The results of this analysis suggest new questions about the investigation of the researched object. In the excerpts analyzed, there was emphasis on the figure of the Holy Spirit, present in all the analyzed speeches as the ultimate goal of the pursuit for those of faith, thus configuring a negative aspect for the figure of the Devil, since being baptized by the Holy Spirit is what guarantees the effective deliverance from the Devil and prosperity in the life of those who believe.